Spiritual Experience and Appraisal as Determinants of Depression and Quality of Life in the Elderly - Lilik Ma’rifatul Azizah; Tri Martiana; Oedojo Soedirham (Health Notions, 2018)
Changes in the elderly due to the aging process caused decrease physical abilities and health conditions. These natural changes may cause depression and lower quality of life in the elderly. Spiritual experience may improve appraisal, reduce depression, and enhance the quality of life. This study aimed to estimate the relationship between spiritual experience, appraisal, depression, and quality of life in the elderly. A randomly selected sample of 100 elderly from 18 villages in Mojokerto East Java. An interview-based questionnaire was used to obtain information about spiritual experience, appraisal, psychological well-being and social relationships. The Index Barthel has used measure activities daily living among elderly. The rate of depression was measured by Geriatric Depression Scale. The relationships among variables were estimated using Structural Equation Model (SEM) run in AMOS program. Spiritual experience had the negative effect of depression (p=0.004). The appraisal was not significantly effected on the level of depression (p=0.13). Depression had the negative effect on quality of life (p=0.03). Spiritual experience had the positive effect on quality of life (p=0.000). Spiritual experience, appraisal, and depression have the positively significant influence on the quality of life, but appraisal was not as the determinant to depression. If the spiritual experience of elderly good, the elderly do not occur depression without any perception of elderly appraisal to a stressor.Keywords: Spiritual experience, Appraisal, Depression, Quality of life, Elderly